(untitled) (Boletin Médico de Postgrado, 2017)
Applanation tonometry is a non-invasive and reproducible method that evaluates the pulse wave, allowing estimation of arterial elasticity in pathology or health conditions affecting the cardiovascular system such as hypertension, diabetes mellitus, dyslipidemia and others. In this study we set ourselves the objective of evaluating, through applanation tonometry, pulse wave velocity, augmentation pressure and augmentation index (IAx) in patients with normal-high blood pressure and high blood pressure. METHODOLOGY: This was a descriptive cross-sectional study with a sample of 90 patients of both sexes, aged between 18 and 70 years. Once the written consent was signed, they were given a complete medical history, physical examination, peripheral arterial pressure and categorized by study group. Later, they were determined by applanation tonometry, using Sphygmocor®, the pulse waveform and parameters central arterial pressures, pulse wave velocity, pulse pressure, augmentation pressure and IAx. RESULTS: It was observed that as increased central blood pressure, especially systolic and arterial pulse pressure increased, the speed of pulse wave, pressure augmentation and IAx, a significantly (P <0.05) and there was a positive correlation (r = 0.2 to 0.5, p <0.05). CONCLUSION: The pulse wave, measured through applanation tonometry, could provide tools for the early detection of vascular alterations in already asymptomatic individuals and / or with established pathology causing arterial stiffness, such as arterial hypertension.